Pengaruh partisipasi anggaran, komitmen organisasi, dan good governance terhadap kinerja manajerial - Purwanti, Erin; Berliani, Kartika (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to examine the effect of Budgetary Participation, Organisational Commitment, and Good Governance on Managerial Performance. The method used is a quantitative method with a descriptive verification approach. The population in this study consisted of 56 respondents. The sample used is non-probability sampling using a saturated sampling approach. To measure the influence of the independent variable on the dependent variable, the classical assumption test, multiple linear regression test, Pearson product-moment coefficient test, determination coefficient test, and hypothesis testing are used partially and simultaneously using the SPSS version 25 application. The results and discussion show that Managerial Performance, Budget Participation, and Organisational Commitment at the Bandung City Health Office are in the "Good" category. While Good Governance at the Bandung City Health Office is in the "Very Good" category. Based on the results of the partial T-Test, Budget Participation has a significant effect on Managerial Performance. Commitment, organization, and good governance have no significant effect on Managerial Performance. Based on the results of the F Test, simultaneously, budget participation, organizational commitment, and Good Governance at the Bandung City Health Office have an effect on Managerial Performance with an influence contribution of 6.038.